Availability Evaluation of a Learning Management Environment - Teixeira, Gervasio Eufrauzino; Nascimento, Erick Barros; Silva Junior, Joao Ferreira da; Maciel, Paulo Romero Martins; Dantas, Jamilson Ramalho (Anais do Workshop sobre Engenharia de Resiliência em Sistemas de Computação (RECS); 2024: Anais do I Workshop sobre Engenharia de Resiliência em Sistemas de Computação, 2024)
Availability analysis is an essential aspect of evaluating a system’s response to different demands. State models and combinatorial models provide a framework for quantitatively assessing availability, helping to identify hot spots and implement risk mitigation strategies. This work proposes developing and validating state space models and combinatorial models to analyze the availability of a Moodle installation in a LAMP stack. Validation of these models allows the construction of study scenarios to improve system uptime and user experience. With the creation of models in Reliability Block Diagrams (RBD) and Continuous-Time Markov Chains (CTMC), it was possible to validate a proposed scenario, achieving an availability of 99.65% with a confidence level of 95%.